2021
DOI: 10.25259/cjhs_26_2021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the knowledge of radiology in exiting medical students in University of Calabar

Abstract: Objectives: Radiology education in the undergraduate level imparts in medical students the basic knowledge to interpret common pathological conditions, know the right imaging requests to make and the right order in which they should be made when they become physicians and the degree of this knowledge is influenced by several factors. The aim of this study was to evaluate the knowledge of radiology in exiting medical students and to identify the challenges of undergraduate radiology education. Material and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Our results are encouraging, as most students are aware of the effects of radiation on pregnancy (94.1%). These findings were consistent with previous studies conducted on Syrians (97.4%) and Nigerians (89.9%), highlighting the importance of this knowledge in medical education [2,6].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are encouraging, as most students are aware of the effects of radiation on pregnancy (94.1%). These findings were consistent with previous studies conducted on Syrians (97.4%) and Nigerians (89.9%), highlighting the importance of this knowledge in medical education [2,6].…”
Section: Discussionsupporting
confidence: 93%
“…This study was consistent with the results presented by a similar study, which found that 47.6% of the participants expressed that the teaching method was inadequate. According to medical students at the University of Calabar, Nigeria, radiology and anatomy should be combined in preclinical courses, as 69.6% strongly agreed or agreed with the idea [ 6 , 14 ]. In addition, the medical students in the Visscher study expressed similar concerns and recommended enhancing the quality of radiology education through both formal and informal exposure [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation